2021
DOI: 10.3390/microorganisms9040757
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenomic Insights into Distribution and Adaptation of Bdellovibrionota in Marine Waters

Abstract: Bdellovibrionota is composed of obligate predators that can consume some Gram-negative bacteria inhabiting various environments. However, whether genomic traits influence their distribution and marine adaptation remains to be answered. In this study, we performed phylogenomics and comparative genomics studies using 132 Bdellovibrionota genomes along with five metagenome-assembled genomes (MAGs) from deep sea zones. Four phylogenetic groups, Oligoflexia, Bdello-group1, Bdello-group2 and Bacteriovoracia, were re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 90 publications
0
10
0
Order By: Relevance
“…In addition, fourteen rare phyla (i.e., representing less than 1% of ASVs across samples) were also found in more than 50% of the samples and are therefore well represented across sub-Saharan African soils. These include the predatory bacterial phylum Bdellovibrionota, previously classified as members of the class Oligoflexia [62], members of which have been proposed to be biocontrol agents in marine environments [63], and Fribrobacteres, a phylum that includes several cellulose-degrading genera [64]. Another rare phylum identified in 589 (of 810) samples, Eremiobacterota (previously known as WS-2), includes several members capable of anoxygenic phototrophy [65] and has been recently associated with the ability to use trace gases such as hydrogen and carbon monoxide as energy sources in exothermic reactions capable of sustaining life in extreme environments [66,67].…”
Section: Ecologically Important Phyla Are Ubiquitous In Sub-saharan A...mentioning
confidence: 99%
“…In addition, fourteen rare phyla (i.e., representing less than 1% of ASVs across samples) were also found in more than 50% of the samples and are therefore well represented across sub-Saharan African soils. These include the predatory bacterial phylum Bdellovibrionota, previously classified as members of the class Oligoflexia [62], members of which have been proposed to be biocontrol agents in marine environments [63], and Fribrobacteres, a phylum that includes several cellulose-degrading genera [64]. Another rare phylum identified in 589 (of 810) samples, Eremiobacterota (previously known as WS-2), includes several members capable of anoxygenic phototrophy [65] and has been recently associated with the ability to use trace gases such as hydrogen and carbon monoxide as energy sources in exothermic reactions capable of sustaining life in extreme environments [66,67].…”
Section: Ecologically Important Phyla Are Ubiquitous In Sub-saharan A...mentioning
confidence: 99%
“…Cand . Puniceispirillum and Pseudofulvibacter (Figure 7B) were probably sustained by decaying phytoplankton (Choi et al, 2015; Gros et al, 2023), whereas Chitinophagales and Oligoflexales might utilize chitinous aggregates (Fontanez et al, 2015; Li et al, 2021; MartĂ­nez‐GarcĂ­a et al, 2022). Aureispira can be attached to gel particles, and feed on bacterial cells or cell debris (Furusawa et al, 2015; Bunse et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Phylogenomic inference showed that both MAGs B11 and B12 fell in the Bdello-group2 in the phylum Bdellovibrionota but form two separate deep branches ( Figure 5 ). Bdello-group2 comprised of the representative Bdellovibrio predators including Bdellovibrio exovorus JSS, Bdellovibrio bacteriovorus HD100, Bdellovibrio bacteriovorus Tiberius, and Bdellovibrio bacteriovorus 109J (Li et al, 2021 ), suggesting that B11 and B12 may also represent bacterial predators. The Bdellovibrionota MAGs B11 and B12 have remarkably smaller genome sizes and lower GC contents than those free-living Bdellovibrionota species ( Supplementary Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Bdellovibrio (in the phylum Bdellovibrionota) and Bdellovibrio -like bacteria (BALOs) are gram-negative bacterial predators living in various environments (Jurkevitch et al, 2000 ; Sockett, 2009 ) and mainly consists of four groups: Bacteriovoracia, Oligoflexia, Bdello-group1, and Bdello-group2 (Li et al, 2021 ). Till now, sponge-associated BALO had only been reported in the shallow-water sponge Cymbastela concentrica , and this predator was proposed to live with cyanobacteria (Tian et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation